Efeito do ácido lático sobre as características microbiológicas, físico-químicas e sensoriais na carne do sol - Nascimento, Evellin Priscila Sousa do (2011)
The dried beef is a food traditionally eaten by Northeastern and has an extensive trade in the city of Natal-RN. It is usually produced in an empirical manner, without any standardization in production. Characterized as partially dehydrated meat product, so that the activity of water present is not sufficient to prevent microbial growth, degradation or the production of microbial toxins. The guarantee that the market dried beef is to provide a quality product hygienic, microbiological, physicochemical and sensory stable and adequate for the safety and consumer satisfaction, which has been increasingly attracted to food with natural preservatives. Thus, the meat industries are replacing the current seasonings and natural preservatives for similar, with it without affecting the shelf life of products. Lactic acid has been used to meet these requirements. In this sense, this study aimed to evaluate the effect of lactic acid on the physico-chemical, microbiological and sensory, besides knowing the consumer profile of dried meat of the City of Natal / RN. The results demonstrated that the use of lactic acid in concentrations of 1% and 2% during the processing of dried meat, had statistically significant effect (p < 0.05) on the physico-chemical (pH and water activity) and consequently reduced the microbial count does not alter the taste of the new product developed. Regarding the results on the consumer profile, it was found that the majority of respondents (71.75%) did not observe the presence of the stamp of the Federal Inspection Service (SIF) to buy this meat food that 81.55% of consumers check the hygiene conditions of the site and handlers, however, a large proportion of respondents not concerned with the guarantee of origin of typical regional products featuring a hazard to food safety for consumers of the city of Natal-RN